(untitled) (Research, Society and Development, 2023)
Objective: verify if reduction of facial convexity obtained with dental extractions promotes changes that are noticeable in frontal view. Compare whether the correction of different degrees of protrusion promotes distinct aesthetic perception in frontal and profile analysis. Methods: two brown female patients with dental class I malocclusion, incisors protrusion and convex profile were selected. Patients displayed initially different protrusion magnitude (moderate x excessive) and were both treated with premolars extraction and anterior teeth retraction. Two sets of images were composed enclosing frontal and lateral records at before and after treatment. Sample of 194 laypeople evaluated the images and answered following questions: (1) Can you notice any differences between the correspondent images presented? (yes or no). (2) Which image do you find most attractive? (3) Assign a score for each image from 0 to 10. Results: position of face had an influence on the perception of the moderate protrusion. In this case, less negative impact on aesthetics was evidenced when protrusion was evaluated frontally. In addition, changes resulting from treatment were more noticeable when analyzed from the profile perspective. Regarding excessive protrusion, no significant differences were observed when comparing frontal and profile views, indicating that protrusion and treatment effects can be perceived equally in both views. Conclusions: treatment with dental extractions in patients with moderate protrusion generates impacts that can be more easily noticed in the profile analysis. However, in patients with excessive protrusion, changes promoted by treatment are noticed in frontal analysis in the same way as in profile.